Intracameral bevacizumab role in trabeculectomy: A 1-year prospective randomized controlled study. Issue 6 (November 2020) - Rabina, Gilad; Barequet, Dana; Mimouni, Michael; Kurtz, Shimon; Shemesh, Gabi; Rosenblatt, Amir; Rosenfeld, Eldar
Purpose: To evaluate the effect of intracameral Bevacizumab on trabeculectomy success rates. Methods: A prospective, randomized, interventional clinical trial. Patients with primary open-angle glaucoma were randomly assigned to two groups: trabeculectomy with mitomycin C and trabeculectomy with mitomycin C and intracameral bevacizumab. Complete success is defined as an intraocular pressure (IOP) reduction of at least 30% from baseline IOP to a measured pressure of between 5 and 18 mm Hg without the use of IOP lowering medications. Qualified success is defined as same achievement of reduced IOP, but with the use of IOP lowering medications. Overall success is defined as same achievement of reduced IOP with or without the use of IOP lowering medications. Results: Thirty-three patients in the mitomycin C group and 36 patients in the mitomycin C and bevacizumab group were included in final analyses. The IOP at presentation was 28.3 ± 8 and 28.4 ± 8.6 mm Hg, compared to 10.8 ± 3.4 and 12.3 ± 3.7 mm Hg at 12 months (p < 0.0001) for the mitomycin C group and the mitomycin C and bevacizumab group, respectively. Complete success at 12 months was achieved in 65% of the mitomycin C group compared to 60% of the mitomycin C and bevacizumab group (p = 0.77). Overall success was achieved in 82% compared to 80% of patients at 12 months (p = 0.78). Both groups showed a statistically significant reduction in IOP after 6 and 12 months (p ⩽ 0.001). There were no statistically significant differences in visual acuity and complications. Conclusion: Intracameral bevacizumab during mitomycin C trabeculectomy in patients with primary open-angle glaucoma apparently does not improve success rates. The adjuvant use of intracameral bevacizumab is therefore not justified.